the The importance of financial planning in preparedness for self-death : The importance of financial planning in preparedness for self-death - farhah hanun ngah ngah (University of Darussalam Gontor Press, 2023)
Unclaimed estate is a major source of economic hardship for Muslims. It may take a long time to liquidate the estate since it could be frozen. The deficiency of knowledge in financial management caused the family to face burdens such as debt of sudden death and not being preparedness for death. Aspect finances are important for individuals and communities in increased well-being of the self, family, and good death. The preparedness for death is important in the face of unexpected things such as chronic illness and sudden death. The research readiness for death based on finances has still been less studied. Is society prepared to have a financial planning readiness for death? Is there a level of understanding among people and communities that death has a financial aspect? In-depth semi-structured discussions with the experts in several domains included readiness for death. This discussion was conducted online, such as via Google Meet, and audio was recorded. This interview was transcribed and coded using an inductive approach. The participants consist of experts in the fields of education and finance. Experts from the National University of Malaysia (UKM), International Islamic University (IIUM), Institute of Islamic Studies Malaysia (IKIM), and University of Science Malaysia (USM). The result is based on a thematic analysis of the preparedness for death-self financial in Malaysia.